Conditional Cash Transfers and the Equity-Efficiency Debate - Das, Jishnu (World Bank, Washington, D.C., 2013)
During the past decade, the use of conditional cash transfers to increase investment in human capital has generated considerable excitement in both research and policy forums. Such schemes are being increasingly adopted in a number of contexts and countries to improve outcomes in health, education, and child labor as they aim to balance the goals of current and future poverty reduction. In this paper, the authors define any scheme requiring a specified course of action in order to receive a benefit as a conditional cash transfer. This definition includes cash transfers based on human capital investments, but is sufficiently broad to encompass other schemes such as work-fare programs or consumption transfers. The authors examine the rationales behind, the problems with, and the tradeoffs inherent to conditional cash transfer programs. They discuss two main concerns: low participation and fungibility. Low participation refers to the problem of program uptake. If individuals do not participate in the program, whether it was designed to increase human capital investment or to target resources, the program will not be successful. The problem of fungibility, however, depends on the rationale for the particular conditional cash transfer program. When used to increase efficiency, even when program uptake is high, program effects may be less than envisioned due to behavioral responses of households that lead to changes in the consumption of close substitutes. While researchers have typically addressed these issues separately, the authors emphasize the need for policymakers to incorporate a number of different factors in a comprehensive framework to design optimal conditional cash transfer schemes.